FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.